Computational Arabic Linguistics: An Example Of Natural Language Processing - Bensafa, Abdelkader (El Omda in Linguistics and Discourse Analysis, 2022)
Computational Arabic Linguistics is a branch of applied linguistics and artificial intelligence that focuses on processing, analyzing, and modeling the Arabic language using computational methods. It is a key application area within Natural Language Processing (NLP), which aims to enable machines to understand and generate human language. Arabic presents unique challenges for NLP due to its rich morphology, complex word formation, diacritics, diglossia (Modern Standard Arabic vs. dialects), and flexible word order. These characteristics require specialized algorithms for tasks such as tokenization, lemmatization, part-of-speech tagging, syntactic parsing, and semantic analysis. In practice, Computational Arabic Linguistics is used in various applications, including machine translation, speech recognition, information retrieval, sentiment analysis, and educational technologies. It plays an important role in improving human–computer interaction for Arabic-speaking users and advancing digital language resources. Thus, it represents a significant example of how Natural Language Processing adapts to the structural and linguistic complexity of different languages, particularly Arabic.